(untitled) (International Journal of Advanced Research in Computer Science, 2017)
In the era of information systems and internet there is more concern rising towards information security in day to day life, along with the availability of the vulnerability assessment mechanisms to identifying the electronic attacks. Traditionally intrusion detection systems (IDS) are classified based on the style of detection they are Using. Ther are two main categories of intrusion detection (ID) those are misuse detection and anomaly detection.This paper mainly concerned about misuse detection system (MDS). In misuse detection, the IDS analyzes the information it gathers and compares it to large databases of attack signatures. Essentially, the IDS looks for a specific attack that has already been documented. Like a virus detection system, misuse detection software is only as good as the database of attack signatures that it uses to compare packets against. Keywords: Intrusion detection system (IDS),Misuse detection system(MDS),pattern matching, Artificial neural network, data mining with fuzzy logic and genetic algorithms.